Perspective of Micro Process Engineering for Thermal Food Treatment - Mathys, Alexander (Frontiers in Nutrition, 2018)
Micro process engineering as a process synthesis and intensification tool enables an ultra-short thermal treatment of foods within milliseconds using very high surface-area-to-volume ratios. The innovative application of ultra-short pasteurization and sterilization at high temperatures but with holding times within the range of milliseconds would allow the preservation of liquid foods with higher qualities, thereby avoiding many unwanted reactions with different temperature-time characteristics. Process challenges such as fouling, clogging, and potential temperature gradients during such conditions need to be assessed on a case by case basis and optimized accordingly. Owing to the modularity, flexibility, and continuous operation of micro process engineering, thermal processes from the lab to the pilot and industrial scales can be more effectively upscaled. A case study on thermal inactivation demonstrated the feasibility of transferring lab results to the pilot scale. It was shown that micro process engineering applications in thermal food treatment may be relevant to both research and industrial operations. Scaling of micro structured devices is made possible through the use of numbering-up approaches; however, reduced investment costs and a hygienic design must be assured.